An annotated checklist of recent non-marine Ostracoda (Crustacea) from Argentina, South America - Sabater, Lara Milena; Monferran, Mateo Daniel; Higuti, Janet; Pérez, Alejandra Patricia (Zootaxa, 2023)
According to an updated list of extant non-marine ostracods, there are 2,330 subjective species in 270 genera in the world, of which 333 species are known from the Neotropical region. However, the knowledge about the ostracod fauna in Argentina is scarce, fragmented and incomplete. Thus, the aim of this study was to present the first checklist of the recent non-marine ostracods from Argentina, including geographical distributions and ecological characteristics of the species. Thus far, 66 ostracod species in 33 genera and 7 families have been recorded in non-marine Argentinian environments. Of the total number of species, 29% can be considered endemic to the country. Most of the species were recorded in alkaline, freshwater to oligohaline cold waters and mainly in low to moderate altitude environments. Our results showed that most studies were mainly carried out in the Pampean and Patagonia region and, therefore, the diversity record of ostracods in Argentina is biased towards these regions.